Extatic phenomena in rituals of Russian mystic religion groups - Welcz, Henryk (Current Problems of Psychiatry, 2012)
Trance is a medical term contained in Chapter V of International Statistical Classification of Diseases and Related Health Problems (ICD – 10) in the part of dissociational disorders (F44.3 together with possession) and denotes a disorder characterised by transitional loss of own identity and decline of complete understanding of the surroundings. In this article I want to deal only with some of the known to me phenomena of trance, dependent on will, performed in Russian mystic religion groups called raskolnicy. Phenomena of trances and ecstasy, which are frequently identified with each other, were named by the researchers of the subject as changed states of conscience and meant particular states caused by physiological or psychological factors, which are characterised by the deviation in subjective understanding of the reality and the change towards the approved forms of behaviour during experiencing them. A trance or a similar state was presented in the activity of the Russian mystic religion groups.